ANALISIS KERJA GRATE COOLER PADA PROSES PRODUKSI SEMEN PADA PT SEMEN BATURAJA Tbk - Prasetyo, Edo; Sidauruk, Josua; Safaruddin, Safaruddin (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2023)
This cooling process should not be skipped because if the heating results in the kiln are not cooled, the results of the cement production are not in accordance with predetermined standards. Grate Cooler is a cooling device, where this tool serves to cool the output clinker from the kiln. In this case, data collection is carried out through interviews, and observing directly to the field and other supporting data such as from books, journals and other literature. The data required for the preparation of the article includes: parts of the grate cooler, instrument data on the grate cooler and the cooling and heating process in the grate cooler. The efficiency of the clinker cooler is the ratio of the amount of heat returned to the kiln with secondary air which becomes kiln combustion air and tertiary air to the amount of heat stored or carried by the clinker when entering the cooler inlet. The higher that is absorbed by the air, the more efficient the cooling process on the clinker. Hot air from the grate cooler output is utilised for secondary combustion air in the kiln, combustion air in the calsiner, drying air in the vertical mill and some will be discharged into the environment which previously passed through the ESP Fan.